Pengaruh Pengekangan CFRP Pada Kolom Beton Mutu Normal dan Mutu Tinggi Bertulangan Bambu Terhadap Kapasitas Beban Aksial dan Deformasi Kolom - Pertiwi, Ziza Ayu; Umniati, B. Sri; Risdanareni, Puput (Universitas Islam 45, 2025)
In the midst of the growing construction projects, the use of composite materials is widely applied, one of which is CFRP (Carbon Reinforced Polymer) which has high tensile strength with low density. The selection of bamboo reinforcement as an alternative material to replace steel is because bamboo has a tensile strength value that is close to the tensile strength of steel. However, bamboo has a weakness in its compressive strength. Therefore, this CFRP restraint is expected to be able to overcome these limitations with the aim of analyzing the effect of CFRP restraint on bamboo reinforced concrete columns with normal concrete quality (25 MPa) and high concrete quality (50 MPa), using CFRP layers of 0 and 2 layers. The experiment was conducted by making 4 square-section concrete columns, using Apus bamboo as the main reinforcement and spiral steel as a binder. After the casting and drying process, the columns were given a CFRP layer according to the variation. The results of the study showed that CFRP restraint could increase the axial load capacity by 6.07% for normal quality concrete columns and 5.58% for high quality concrete columns. In addition, normal quality concrete columns with CFRP restraints also reduce the maximum deformation value by 47.6% and for high quality concrete columns it reduces the maximum deformation value by 87.3%.